(untitled) (Herald of the National Children’s Medical Center, 2024)
Hydatid echinococcosis of the liver is a widespread parasitic disease in humans, which is much more severe in childhood than in adults. During the course of the disease, the development of various complications is possible, among which an important place is occupied by rupture of the wall of the liver cyst with the development of peritonitis and anaphylactic shock, which determine the severity of the patient’s condition. The developed serious complication requires adherence to rational treatment tactics aimed at preparation, gentle surgical treatment, postoperative management and prevention of disease relapse.